PELATIHAN ORAL HYGIENE PADA PETUGAS DAN PENDAMPING PASIEN BIBIR SUMBING DI YAYASAN SENYUM, SANGLAH, DENPASAR - Ni Putu Giri Karmany; Ni Ketut Natalia Kristianingsih; Ni Kadek Danis Lisyaningsih; Desak Made Widyanthari (Coping: Community of Publishing in Nursing, 2016)
Oral hygiene is one of the important procedure, especially for the cleft lip/palate patients. However, the cleft lip/palate patients in Smile Foundation of Bali don’t perform the proper oral hygiene. According to the observation, it happens because the officers and patients escort has the lack of knowledge and ability in performing oral hygiene. Based on this situation, oral hygiene training is required for the officers and patients escort at the Smile Foundation. The main purpose of this activity is to improve the knowledge and the ability of officers and patients escort in performing oral hygiene to the cleft lip/palate patients. Oral hygiene training conducted from April 30th, 2016 to June 25th, 2016. The training participants were consist of 10 officers and 19 patients escort. The technical explanation was given to the officers and patients escort before the training was conducted. Evaluation is required after the training process. Evaluation was conducted by giving some question to the participants. Besides that, it conducted by doing the observation. The observation process is guided by the Standard Operational Procedure (SOP). The oral hygiene training is beneficial to improve the knowledge and the ability of officers and patients escort in performing oral hygiene to cleft lip/palate patients. Flipchart dan education videos were also given to the Foundation parties in order to support the training process. Monitoring was conducted to ensure the sustainability of the program. The program sustainability at the Smile Foundation is expected. Another oral hygiene training technique is also recommended for the cleft lip/palate patients. Keywords: Cleft Lip/Palate, Oral Hygiene Training